An unexpected discovery of Stactobiella risi (Felber, 1908) (Trichoptera, Hydroptilidae) in Kosovo with notes on its habitat - Halil Ibrahimi; Astrit Bilalli; Donard Geci; Milaim Musliu (Journal of Insect Biodiversity and Systematics, 2024)
Caddisfly sampling conducted during 2023 in the Bistrica e Shalës River, belonging to the Ibër basin and in the Mirusha River, belonging to the Drini i Bardhë (White Drin) basin, revealed the first record of Stactobiella risi (Felber, 1908) for Kosovo and for Ecoregion 5 (Dinaric Western Balkans). Previously, this species had only been known from few localities in Europe. The morphology of the male genitalia in the collected specimens generally corresponds to the described species, with the exception of a less apically elongated inferior appendages in lateral view, which may be attributed to geographical variability. This discovery increases the knowledge about the distribution of family Hydroptilidae in Kosovo and the Balkans. In addition to this we provide a list of sympatric species in both localities including few rare species such as Hydropsyche botosaneanui Marinković Gospodnetić, 1966 and Rhyacophila macedonica Karaouzas, Valladolid & Ibrahimi, 2022.